Evaluation of the Influence of Communication Aspects and Leadership Competence in Decision Making to Improve Performance in Housing Developers - Gifson Sirait; Endah Kurniyaningrum (Eduvest - Journal of Universal Studies, 2025)
The construction industry, particularly in housing development, plays a strategic role in meeting the need for adequate housing, supporting economic growth, and improving the quality of life for communities. However, the implementation of housing projects faces complex challenges, such as pressure to meet high quality standards, tight schedules, and limited budgets. Factors such as communication aspects and leadership competence play a significant role in decision-making to enhance project performance. This study aims to analyze various factors that influence the quality and performance of projects in housing development, including the influence of communication and leadership competence in decision-making to improve project performance. In addition, this research also evaluates the relationship between decision-making and project performance, as well as the mediating role of decision-making in the relationship between communication aspects and leadership competence on project performance. This study uses a quantitative approach with a survey method. Data were collected through a closed-ended questionnaire using a Likert scale and analyzed using statistics. The analysis includes descriptive analysis and PLS-SEM (Partial Least Squares Structural Equation Modeling), covering both the outer model and inner model measurements. The results of this study revealed a significant relationship between communication aspects and project leadership competencies on decision-making, as well as the impact of decision-making on overall project performance with a percentage of 73.6%. Furthermore, decision-making plays an important mediator in strengthening the relationship between the two variables of communication aspects and project leadership competencies with project performance with a percentage of 49.4%.